Discovery of novel and highly potent dual-targeting PKMYT1/HDAC2 inhibitors for hepatocellular carcinoma through structure-based virtual screening and biological evaluation - Yang, Yang; Wang, Yuting; Chen, Jing; Niu, Miao-Miao; Wang, Yongbin; Jin, Xing (Frontiers in Pharmacology, 2024)
Simultaneous inhibition of two or more pathways is playing a crucial role in the treatment of hepatocellular carcinoma with complex and diverse pathogenesis. However, there have been no reports of dual-targeting inhibitors for protein kinase membrane-associated tyrosine/threonine 1 (PKMYT1) and histone deacetylase 2 (HDAC2), which are critical targets for hepatocellular carcinoma treatment. Here, an integrated strategy of virtual screening was utilized to identify dual-targeting inhibitors for PKMYT1 and HDAC2. Notably, PKHD-5 has been identified as a potent inhibitor that selectively targets both PKMYT1 and HDAC2 with nanomolar affinity. Molecular dynamics have confirmed the strong binding stability of PKHD-5 with PKMYT1 and HDAC2. Importantly, it displayed a notably lower IC50 against the HepG2/MDR cell line, underscoring its potential to surmount drug resistance, while exhibiting minimal toxicity towards the normal liver cell line L02. Additionally, PKHD-5 has demonstrated significant antitumor proliferation effects without significant toxicity. In summary, the results suggest that PKHD-5 is a promising candidate for further preclinical studies of hepatocellular carcinoma therapy.